Phillipson's Linguistic Imperialism Revisited at the light of Latin American Decoloniality Approach - Luis Guillermo Barrantes-Montero (Universidad Nacional, Costa Rica, 2017)
A summary of the book Linguistic Imperialism, by Phillipson (1992)2 is presented here. The purpose is to highlight its current scope and permanent values in consonance with intuitions, criticism and alternatives proposed by Latin America Modernity/coloniality Group. Criteria of analysis are based on a re-reading of the work in the light of the decolonial perspective, with the aim of proposing pedagogical insights which guide language and literature teachers in approaching their study contents with a critical vision. The idea is to remark the role of English Language Teaching for the maintenance of power structures and for its potential for creating new epistemological approaches to language teaching and learning. An epistemological turnaround in the linguistic formation of future educational personnel is a must for that end.